Иштван Киш: [альбом] / И. Е. Светлов - Светлов Игорь Евгеньевич (Прогрессивные художники мира, 1978)
Экземпляры: ИСК (20111025) / Инвентарный номер: 688510 / Цена: 0.50 / Сис.шифр: 85.133(3/8) / Авт.знак: С 24 / ГРНТИ: 18 / ББК: 85.133(3/8)-8